Photoluminescent Detection of Human T-Lymphoblastic Cells by ZnO Nanorods - Tamashevski, Alexander; Harmaza, Yuliya; Slobozhanina, Ekaterina; Viter, Roman; Iatsunskyi, Igor (MDPI: Molecules, 2020)
The precise detection of cancer cells currently remains a global challenge. One-dimensional (1D) semiconductor nanostructures (e.g., ZnO nanorods) have attracted attention due to their potential use in cancer biosensors. In the current study, it was demonstrated that the possibility of a photoluminescent detection of human leukemic T-cells by using a zinc oxide nanorods (ZnO NRs) platform. Monoclonal antibodies (MABs) anti-CD5 against a cluster of differentiation (CD) proteins on the pathologic cell surface have been used as a bioselective layer on the ZnO surface. The optimal concentration of the protein anti-CD5 to form an effective bioselective layer on the ZnO NRs surface was selected. The novel biosensing platforms based on glass/ZnO NRs/anti-CD5 were tested towards the human T-lymphoblast cell line MOLT-4 derived from patients with acute lymphoblastic leukemia. The control tests towards MOLT-4 cells were performed by using the glass/ZnO NRs/anti-IgG2a system as a negative control. It was shown that the photoluminescence signal of the glass/ZnO NRs/anti-CD5 system increased after adsorption of T-lymphoblast MOLT-4 cells on the biosensor surface. The increase in the ZnO NRs photoluminescence intensity correlated with the number of CD5-positive MOLT-4 cells in the investigated population (controlled by using flow cytometry). Perspectives of the developed ZnO platforms as an efficient cancer cell biosensor were discussed.
Keywords: zinc oxide nanorods; MOLT-4 cell line; T-lymphoblasts detection; cluster of differentiation proteins; monoclonal antibody anti-CD5; room temperature photoluminescence